The employment of Arabic script in contemporary Iraqi Plastic Art: Sculpture as a model - Mustafa Ali Assi (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2026)
The letters inscribed at the beginnings of the Quranic chapters led the researcher to delve into their mysteries and secrets, prompting a serious investigation into the importance, significance, and sanctity of these letters, as well as the profound emotions, historical significance, and cultural references they embody. This includes exploring the ideas and stages these ideas have undergone to manifest in various themes within contemporary Iraqi art in general, and sculpture in particular. The experience of this art form has been a source of debate due to its theoretical and practical dimensions. The letters inscribed in artworks, whether as words, letters, symbols, or subtle signs, formed focal points that the researcher focused on, making them a central element in his research. The research, which includes four chapters, explores the relationship between individuals and artists, highlighting their creative abilities. The first chapter presents the problem, defined by the question: What are the manifestations of Arabic script in contemporary Iraqi art? The importance of the research and the need for it were presented. The aim of the study was to recognize the manifestations of Arabic script in contemporary Iraqi art. Chapter Two contained three sections: the first (the historical roots of Arabic script), the second (the use of Arabic script by Muslims), and the third (the formative features of Arabic script). Chapter Three dealt with the framework of the research procedures. The study population consisted of (25) works, and the sample amounted to five artworks. The researcher adopted the content analysis method as a methodology. Chapter Four: Results and Conclusions dealt with the results. The cultural and aesthetic importance of the letter lies here in the artist’s use of it, moving between diverse connotations and different forms of representation and colors that carry different meanings. In the face of all this great gift that the Arabic letter is adorned with in terms of continuity and freedom of movement, has the Iraqi artist in particular fulfilled his right and how did he derive from it the intellectual aesthetic characteristics in his artistic contribution.